A Study to Put the Foundations of Cadastre Modeling in Syria - زوباري, علي; شعبان, فادي; حسن, يانا (Latakia University Journal -Engineering Sciences Series, 2020)
Data models are one of the main elements of three dimensional cadasteral information systems, and the basis for creating databases that help maintaining and developing data as needed over time. The purpose of this research is to explore the followed foundations for building the most common cadastral data models in the world, looking at how these models manage three-dimensional legal data (rights, restrictions, and responsibilities), and finding out the best way to document these models. When determining the foundations used globally, we can use it to create a syrian cadastral data model, wich supports three-dimensional cadastral requirements, and provides a basis for creating a database of all kinds of three-dimensional rights, restrictions and responsibilities. In this research, five cadastral models available have been studied, and the following points were check how these models manage 3D data, specifically stratified rights, how to realize the requirements of 3D cadaster, what are techniques that used to present these models, and the structure which used to connect their elements to each other. Therefore, the most important questions were asked about the model management of the data, such as determining the basic spatial unit, and basic elements of the model, and knowing its data sources were answered.